First Measurements of Ambient PM2.5 in Kinshasa, Democratic Republic of Congo and Brazzaville, Republic of Congo Using Field-calibrated Low-cost Sensors - Celeste McFarlane; Paulson Kasereka Isevulambire; Raymond Sinsi Lumbuenamo; Arnold Murphy Elouma Ndinga; Ranil Dhammapala; Xiaomeng Jin; V. Faye McNeill; Carl Malings; R. Subramanian; Daniel M. Westervelt (Aerosol and Air Quality Research)
Abstract Estimates of air pollution mortality in sub-Saharan Africa are limited by a lack of surface observations of fine particulate matter (PM2.5). Despite being large metropolises, Kinshasa, Democratic Republic of the Congo (DRC), and Brazzaville, Republic of the Congo (ROC), which possess populations of 14.3 million and 2.4 million, respectively, use no reference air pollution monitors at the time of writing. However, a few reference monitors have recently been deployed in other parts of sub-Saharan Africa, including a Met One Beta Attenuation Monitor (BAM-1020) at the U.S. Embassy in Kampala, Uganda, next to which a low-cost PM2.5 monitor, the PurpleAir, was collocated in August 2019. The raw PurpleAir data from September 2019 through February 2020 strongly correlated with the BAM-1020 measurements (R2 = 0.88) but also exhibited a mean absolute error (MAE) of approximately 14 µg m−3. Employing two calibration models, namely, multiple linear regression and random forests, decreased the MAE to 3.4 µg m−3 and increased R2 to 0.96. Given the similarity in climate and emissions, we applied the collocated field correction factors for Kampala to four PurpleAir units in Kinshasa and one in neighboring Brazzaville, which were deployed in April 2018. We estimated an average annual PM2.5 concentration of 43.5 µg m−3 in Kinshasa for 2019, which exceeds the World Health Organization (WHO)’s Interim Target 1 (10 µg m−3) by 4 times. Finally, the surface PM2.5 level and the aerosol optical depth were about 40% lower during the COVID-19 lockdown in 2020 than the corresponding period in 2019, which cannot be attributed solely to changes in meteorology or wildfire emission. Hence, our results highlight the need to implement clean air solutions in the Congo.